SOLAR PHOTOVOLTAICS CONTRIBUTION TO ENERGY MIX IN SELECTED NIGERIAN ESTATES - Adepoju, Adeyemi; Jesuleye, Olalekan; Arigbede, Olutosin (Archives of Business Research, 2020)
This paper assessed the share of Solar Photovoltaics (PV) in the energy mix for various energy services in Nigerian residential estate. Model for Analysis of Energy Demand (MADE-II) was used to analyze the primary and other secondary data obtained for the study. The results showed that the current contribution of solar PV in energy demand split for the estates was still low, with a total share of 8.8%, 6.7% and 4.4% in Ijapo, Alagbaka and Sunshine Housing Estate despite various government interventions. Its usage level constituted an insignificant share of 27.9%, 57.3%, 18.3%, 0%, 0%, 0%, 0%, and 16.8% for the total lighting, computing/internet, entertainment, process heat, cooking, refrigeration, water pumping and ventilation services requirement respectively in Ijapo Housing Estate, 26.5%, 70.6%, 13.7%, 0%, 0%, 0%, 0%, and 16.5% in Alagbaka Housing Estate, and 24.0%, 50%, 14.1%, 0%, 0%, 0%, 0%, and 1.8% in Sunshine Housing Estate. The study concluded that utilization of solar PV as an energy source for energy service ensure access to affordable, reliable, sustainable and modern energy for all. The research recommended that government support for solar PV intervention should be further encouraged.